Penggunaan Sistem Aplikasi Redmine Dan Subversion Dalam Manajemen Proyek - Corie Mei Hellyana - AMIK BSI Purwokerto (Universitas Bina Sarana Informatika, 2015)
Abstract The level of progress of the internet today is growing rapidly making it possible to communicate across various regions without knowing the time. In the process of managing a very necessary project team work, which must communicate with each other. Given the development and progress of the internet, communication is built by a team work can be done without having to meet in person. In building a software system project is not easy, this is because the level of consumer demand that is increasingly growing complex, but it is also the development of application software itself, which grew in number and should always be update. With the project management, a manager can know and see the bugs each personnel and analyze the course of the project. An alternative applications of project management system that can be used is Redmine. Redmine application is a web-based application, where the application can be accessed by all members of the team and must be on the same computer network. Some of the advantages possessed by Redmine that use a lot of projects / issues, regulatory control access, search issues, project statistics, project schedule, filing of documents (both documents old / new), notification via email or xml, merging with Subversion. Keywords: Project Management, Subversion, Redmine.